Implementation of AES-256 Algorithm in Android-Based E-Voting Data Security - Faiz Nazhir Amrulloh; Yuli Asriningtias (Jurnal Penelitian Pendidikan IPA, 2023)
E-voting is a method of voting and vote counting in general elections using digital devices. There are still many errors and fraud that occur during village head elections in Indonesia. Then the idea was created to carry out village head elections by utilizing existing technological developments, especially Android-based smartphone technology. The data source used in this study is secondary data which uses population data of citizens who will exercise their right to vote, vote data for citizens' voting rights, and data from the results of vote acquisition during the village head election process. In this study, a number of important data were needed in the village head election process which was carried out using documentation techniques. This research produced an Android-based application system for securing e-voting data for village head elections using the AES-256 cryptographic algorithm called Vodes. The application produced in this study was built using the Kotlin programming language on the Android frontend side by utilizing the Android Studio IDE as a tool in the development process. While on the backend side it uses the Javascript programming language using the Node js framework. The database used in the Vodes application uses MySQL. Based on the results of this study, it can be concluded that an e-voting data security application for village head elections has been created using the AES-256 cryptographic algorithm. The application produced in this study has succeeded in properly securing all aspects of the data in the village head election process